PEMANFAATAN LIMBAH RUMAH TANGGA MENJADI KOMPOS (KOLIRUTA) DENGAN KEMASAN RAMAH LINGKUNGAN DI KOTA PAGAR ALAM - Masdalipa, Risnaini; Dhiniati, Fameira; Erika, Desta Ria (LPPM Universitas Bina Bangsa, 2024)
It is known that there is no Temporary Waste Disposal Site (TPS) provided in Karang Dalo Village, Dempo Tengah District, Pagar Alam City. The unavailability of TPS has the potential to breed disease vectors such as flies, insects, dogs and so on. Waste that is simply thrown away without being processed first will have a negative impact on public health. There is also waste that is destroyed by burning, but burned waste can cause health problems. This service is carried out so that the community has knowledge about how to process waste more usefully by applying computer technology in processing organic waste into compost. The community service program entitled Utilization of Household Waste into Compost (KOLIRUTA) with environmentally friendly packaging in Pagar Alam City aims to provide solutions to problems faced by the community related to the processing and marketing of compost. This program also aims to provide specific services and solutions for partners who are not economically or socially productive